PENGEMBANGAN APLIKASI KARTU RENCANA STUDI ONLINE PADA JURUSAN PENDIDIKAN LUAR SEKOLAH UNIVERSITAS PALANGKA RAYA - Widiatry, Widiatry (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2020)
Kartu Rencana Studi is an important activity carried out by students to determine the courses to be taken in the following semester, the process of filling out Kartu Rencana Studi is done one week before the lecture is really active and if students do not fill out in accordance with applicable regulations, the student concerned is considered on college leave. In the Department of Non-School Education, the University of Palangka Raya to fill in Kartu Rencana Studi still uses a manual method where students consult with their academic supervisor to ask for approval of the courses to be programmed in the semester that will take place. In the implementation of this filling process can cause problems, one of which is the delay of students in completing Kartu Rencana Studi, it is difficult to control the courses taken by students, not all courses that want to be programmed in accordance with the courses issued and there are some specific subjects who experience conflicts on the same scheduled day and hour make students have to readjust the schedule and courses to be taken with the available schedule. This research design made up of two stages: (1) data collection and analysis conducted by means of literature study and observation, (2) applying the waterfall method already modified with the stages is system analysis, design, implementation and testing. The implementation uses PHP and Mysql as a database to store data. Furthermore, at this testing stage using the Blackbox method.